Analisis Pendapatan, Daya Saing dan Dampak Kebijakan Pemerintah Terhadap Usaha Peternakan Sapi Perah Rakyat di Kabupaten Pelalalawan - Hendri Hendri (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2021)
The development of dairy cows in Pelalawan District is integrated with plantation crops (cow-oil). Riau Province has the largest oil palm plantation in Indonesia, which is 2.706 million hectares, so it has a potential source of feed for dairy cattle and is expected to have an impact on the competitiveness of cattle farming in Riau. The research was conducted on the people's dairy farming business in Pelalawan Regency, with the aim of knowing the level of profit, competitiveness and impact of government policies on dairy farming using the Policy Analysis Matrix (PAM). The results showed that the average private breeders' profit was Rp. 19,481,081.55/head/lactation and social benefits of Rp. 20,431,492.21/head/lactation. Smallholder dairy farming in Pelalawan Regency has good competitive competitiveness (PCR=0.25) and comparative competitiveness (DRCR=0.24). Dairy farmers receive input subsidies from the government with an NPCI of 0.79 and are also burdened with an output tax with an NPCO of 0.93. Overall, government policies have not provided incentives (disincentives) for dairy farming in Pelalawan District with an EPC of 0.96.